Evaluation of Serum Concentration of Copeptin, Resistin, Irisin and Some Immunogical Variables in Polycystic Ovary Syndrome Infected Patients in Kirkuk City - Hameed, Nagham Imad Abdul; Al-doory, Zina Abdulmunem Abdulrazaaq (American Journal of Biology and Natural Sciences, 2024)
Background: Polycystic ovary syndrome is most common disorder in the endocrine system in women of fertile and reproductive age, as it is associated with irregular menstruation, indicators of insulin resistance, and androgen excess. . Objective: The current study was designed to evaluation of Polycystic ovary syndrome-PCOS infection effects on some variables such as Copeptin, Resistin and Irisin, Luteinizing hormone-LH, Folic stimulating hormone-FSH, Testosteron . Methods: The study was conducted on 50 patients infected with PCOS and 30 healthy women (uninfected ), who attended the Al-Jumhuri general hospital of Kirkuk city from 15/5/2024-15/6/2024. The results : results showed a significant (P<0.05) increase in serum level of (Copeptin, Resistin and Irisin, LH, T.T ) and a significant decrease in level of (FSH) in PCOS infected patients compered healthy women . Conclusion: Copeptin, Resistin, Irisin and some variables are important physiological and immunogical biomarkers that can support the diagnosis of PCOS.